Literature Review: Intervensi dalam Mengatasi Stigma-Diri pada Pasien HIV/AIDS - Avin Maria (STIKes Panti Rapih, 2020)
Introduction: Self stigma in people living with HIV/AIDS is a survival mechanism to protect themselves from external stigma. Stigma and discrimination in people living with HIV/AIDS can lead to inequality in sociallife. This inequality can cause inferiority complex, preoccupation, and denial of diagnosis, which correlates with the onset of depression. Objective: To review an intervention that can be use to reduce self stigma on people living with HIV. Methods: Researcher conducted a literature review of studies and reports that assessed the effectiveness of interventions to reduce HIV self-stigma. Databases searched from Science Direct, EBSCO Host, PubMed, and Google Scholar. Article criteria is article which published from 2010-2019. Results: Of 117 articles and reports identified, 3 were included in review representing 4 different interventions which used on reduce self-stigma on peple living with HIV. The interventions are logo therapy, Acceptance and Commitment Therapy (ACT), Family psycoeducation, Stigma Reduction Intervention (SRI). Conclusion: This literature review showed that stigma reduction intervention with workshop, logotherapy, ACT, FPE and stigma reduction intervention with video can reduce self stigma on HIV patients. There is a need for policies to be able to implement these interventions because through the reduction in selfstigma, the effect is in improving patient health and patient medicationadherence. All intervention are promising nterventions to reduces self- stigma because applicable and feasible to implement due to its flexibility, non-invasive and no side effects. Keywords: literature review, HIV, self stigma